The radicalism of modesty: democracy and art in Camusian thought (1945–1951). Issue 3 (3rd April 2019) - Visone, Tommaso
ABSTRACT: Albert Camus has rarely been considered as a theoretician of democracy. Nonetheless, from the end of the Thirties it is possible to find in his different writings several observations relating to politics and the life of democracy and democracies. The second half of the Forties saw this interest, intertwined with the new post-WWII context, being explicitly dedicated to such subjects in the form of several articles and observations. Through the latter, Camus developed a radical – literally 'that goes to roots' – analysis of twentieth century politics, defining an identity between democracy and modesty and using them to face the nihilistic attitude spread by totalitarian regimes and 'conquering spirits' within the same western society. Such attention to 'modesty' was also defined in direct connection with the idea that Camus developed during the same period on the concept of Art and the role of the artist. According to Camus, the artist – or the 'eternal girondin' – is like a democrat who tries to defend pluralism and unity against homologation and totality. Through tracing the historical growth of such a reflection and its relevance in defining some critical issues, this study leads us to a better understanding of contemporary politics and its crisis.